Implementation of New Public Service (NPS) Principles in Identity Document Issuance Services in Periuk Jaya Urban Village, Tangerang City - Sari, Putri Alfiyyah; Tazkia, Siska Rahayu Indri; Hasanah, Tamimatul; Kurniawan, Irvan Arif (Journal of Public Representative and Society Provision, 2025)
This study examines the implementation of the New Public Service (NPS) principles in providing Digital Population Identity (IKD) services in Periuk Jaya Village, Tangerang City. NPS principles emphasize public service based on community needs, citizen participation, and transparency. The research employed a descriptive qualitative method, utilizing primary data from in-depth interviews and observations, as well as secondary data from official documents. The findings reveal that Periuk Jaya Village has endeavored to implement NPS principles through IKD benefit socialization, infrastructure enhancement, and technical training for village officials. However, challenges remain, including limited public understanding, inadequate technological infrastructure, and administrative complexities. Recommendations include more inclusive socialization, technological infrastructure development, and continuous training for officials. Implementing NPS principles is expected to foster public services that are more responsive, inclusive, and community-oriented.